The Teachig Environment in Level Eight Basic Classes at Public and Private Schools in Erbil City Center (Investigation and Contrustive Study) - Halliz Antar Walle; Sarween Younis Othma (Zanco Journal of Humanity Sciences)
the study is aimed at The Teachig Environment in Level Eight Basic Classes at Public and Private Schools in Erbil City Center (Investigation and Contrustive Study) the researcher has followed the descriptive method in her research, and the research population consists of eighth grade students in public and private schools in the center of Erbil for the academic year (2022-2021), The sample of the study has randomly been selected from public and private schools. The overall number of the sample comprises 200 subjects, 100 students from public schools and 100 students from private schools.To achieve the objectives of the study, a close–ended questionnaire has been used,it is a teaching environment scale which consists of 45 items and is divided into three dimensions: physiological environment, social environment and physical environment, After collecting the data and analyzing them by using SPSS programme, the researcher reached the following conclusions: There is a statistically significant difference at (0.05) in the teaching environment between public and private schools at Erbil city center and the difference is in favour of schools .